1995
DOI: 10.1046/j.1365-313x.1995.07010109.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted recombination in plants using Agrobacterium coincides with additional rearrangements at the target locus

Abstract: The use of Agrobacterium for gene targeting in plants has been investigated. Leaf protoplasts of five transgenic tobacco lines, containing a T-DNA insertion with a defective npt-II gene at different positions in the plant genome, were transformed via Agrobacterium with a T-DNA containing a npt-II repair gene. After selection for kanamycin resistance and PCR analysis six recombinants were derived from four of the target lines. The recombination frequencies were similar for the different target lines with one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 0 publications
6
51
0
Order By: Relevance
“…This process seemed to be restricted to the target locus itself in one case, whereas in the other two cases also sequences flanking the target locus were included. Similar events have been described before in tobacco (27,28).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This process seemed to be restricted to the target locus itself in one case, whereas in the other two cases also sequences flanking the target locus were included. Similar events have been described before in tobacco (27,28).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the modified nptII gene had to reside in an additional T-DNA copy in which the incoming T-DNA was converted by the target locus and then integrated elsewhere. This phenomenon was described before for plants (27,28) and mammals (29) as ectopic targeting. Further PCR analyses showed that two of these modified target locus copies also contained the flanking tobacco DNA sequences of the original B18͞4 locus.…”
Section: Resultssupporting
confidence: 57%
“…In most of these studies, DNA was introduced into cultured cells by direct gene transfer (10,11) or Agrobacterium-mediated transformation (12)(13)(14)(15). In general, GT efficiencies were low, on both a per-cell basis (Ͻ10 Ϫ7 GT events per cell) and per-integration basis (10 Ϫ6 to 10 Ϫ4 GT events per integration), and negative selection to select against random integrations was not successful (16)(17)(18)(19).…”
Section: ϫ5mentioning
confidence: 99%
“…The number of gene-targeting events detected in early studies in plants was too small to permit a statistically reliable estimate of gene-targeting efficiency (3)(4)(5)(6)(7)(8). The recent report of several additional gene-targeting events in two studies has made it possible to estimate the gene-targeting frequency with greater accuracy.…”
mentioning
confidence: 99%